Oxidized regenerated cellulose gauze as a hemostat in infantile hypertrophic pyloric stenosis - Gupta, Rahul; Bhandari, Anu (Journal of Neonatal Surgery, 2020)
Background: The Ramstedt pyloromyotomy is a standard procedure for infantile hypertrophic pyloric stenosis (IHPS). However, continuous postoperative bleeding may occur from the pyloromyotomy site without the use of any hemostatic management. We aim to analyze the pre-operative and post-operative hemogram values with and without the use of oxidized regenerated cellulose gauze as a hemostat in IHPS. Methods: A prospective study performed from January 2019 to March 2020. The patients were randomly distributed by chit method into two groups: Group A (Control) without the use of hemostat and Group B (Case) with oxidized regenerated cellulose gauze as a hemostat. Results: There were 26 patients with 19 males and 7 females. There were 13 patients in Group A and 12 in Group B; while one patient succumbed before surgery. Ramstedt’s pyloromyotomy was performed in 25 (96.16%) patients. A total of 7 (28%) postoperative complications were recorded in our patients. One patient in group A with intraperitoneal blood collection required blood transfusion for anemia caused by peritoneal bleeding. There was one postoperative death (group A). Significant statistical differences between preoperative and postoperative RBC (106/mm3), hemoglobin (g/dl), and hematocrit (%) levels were observed in group A but insignificant differences among the values in group B. Conclusions: We recommend that oxidized regenerated cellulose should be applied to the pyloromyotomy site to minimize perioperative bleeding associated with the Ramstedt procedure. It appears to be a safe, easily available, easy to use, and effective hemostatic agent available for IHPS.